(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review explores the impact of excess weight on reproductive system development in male adolescents, highlighting hormonal imbalances, altered pubertal timing, and long-term fertility risks. Overweight status disrupts the hypothalamic-pituitary-gonadal axis through mechanisms like increased aromatase activity and altered gonadotropin levels, leading to reduced testosterone and relative hypogonadism. Obese boys may show early testicular growth but delayed secondary sexual development. These changes can impair adult fertility, emphasizing the need for early diagnosis and effective weight management. The review is based on scientific studies published between 2020 and 2024, offering guidance for clinical practice and future research in pediatric reproductive endocrinology.